2017
DOI: 10.1261/rna.060541.116
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution profiling of NMD targets in yeast reveals translational fidelity as a basis for substrate selection

Abstract: Nonsense-mediated mRNA decay (NMD) plays an important role in eukaryotic gene expression, yet the scope and the defining features of NMD-targeted transcripts remain elusive. To address these issues, we reevaluated the genome-wide expression of annotated transcripts in yeast cells harboring deletions of the UPF1, UPF2, or UPF3 genes. Our new RNA-seq analyses confirm previous results of microarray studies, but also uncover hundreds of new NMD-regulated transcripts that had escaped previous detection, including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
146
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(171 citation statements)
references
References 80 publications
(122 reference statements)
23
146
2
Order By: Relevance
“…Consistently, previous studies have shown that UPF genes are involved in more than just the degradation of nonsense messages, but rather target a wide range of mRNAs, including aberrant and normal ones (He et al 2003;Hug et al 2015). In line with this, substrates of Upf proteins have lower codon optimality (Celik et al 2017). Furthermore, we did not observe any change of effect upon knockout of DOM34 and HBS1 (Fig.…”
Section: Several Sequence Features In Thesupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, previous studies have shown that UPF genes are involved in more than just the degradation of nonsense messages, but rather target a wide range of mRNAs, including aberrant and normal ones (He et al 2003;Hug et al 2015). In line with this, substrates of Upf proteins have lower codon optimality (Celik et al 2017). Furthermore, we did not observe any change of effect upon knockout of DOM34 and HBS1 (Fig.…”
Section: Several Sequence Features In Thesupporting
confidence: 92%
“…2D). These observations are consistent with a single-gene study demonstrating that translation of upstream ORFs can lead to RNA degradation by NMD (Gaba et al 2005) and that uORFs are enriched in NMD substrates (Celik et al 2017). Altogether, these results show that uAUGs are mRNA destabilizing elements as they almost surely match with cognate premature stop codons, which, whether in frame or not with the gene, and within the UTR or in the coding region, trigger NMD.…”
Section: Upstream Augs Destabilize Mrnas By Triggering Nonsense-mediasupporting
confidence: 89%
“…In lower eukaryotes such as yeast, short (< 200 nt), homogenous 3 0 UTRs make surveillance of 3 0 UTR length an effective strategy to identify PTCs (Jan et al, 2011;Celik et al, 2017). In contrast, mammalian mRNAs are subject to extensive post-transcriptional regulatory mechanisms that combine to determine their stability, translation efficiency, localization, and function.…”
Section: Introductionmentioning
confidence: 99%
“…Page 6, third paragraph: More recent investigations of yeast NMD have not uncovered evidence for a downstream sequence element that contributes significantly to decay target discrimination 8 , 15 . …”
mentioning
confidence: 99%
“…The author should also mention a recent paper in yeast describing that poor translation efficiency is a major criteria for NMD targeting (Celik et al, 2017 2 ). This major result could potentially explain not yet understood deregulations observed in several other species upon NMD knockdown.…”
mentioning
confidence: 99%